Solubility of hydrocarbons in water: Experimental measurements and modeling using a group contribution with association equation of state (GCA-EoS) - Pereda, Selva (2009)
In this communication, new experimental data on the solubility of n-hexane, cyclo-hexane and iso-octane in pure water are reported. The data have been measured using a static-analytic technique that takes advantage of a Rolsi™ sampling device in the temperature range of 298-353 K and at pressures up to 0.5 MPa. The experimental data measured in this work at 298 K have been compared with some selected data from the literature and good agreement is found. A group contribution plus association equation of state, namely the GCA-EoS, is used to model the phase equilibrium of water + hydrocarbon (C2 to n-C6, cy-C6, i-C4 and i-C8) system. The predictions of the model are found in good agreement with the experimental data measured in this work and some selected data from the literature. © 2008 Elsevier B.V. All rights reserved.